Theoretical investigations into the variability of the 15N solid-state NMR parameters within an antimicrobial peptide ampullosporin A - Czernek, J; Brus, J (Physiological research, 2018)
The solid-state NMR measurements play an indispensable role in studies of interactions between biological membranes and peptaibols, which are amphipathic oligopeptides with a high abundance of alpha-aminobutyric acid (Aib). The solid-state NMR investigations are important in establishing the molecular models of the pore forming and antimicrobial properties of peptaibols, but rely on certain simplifications. Some of the underlying assumptions concern the parameters describing the 15N NMR chemical shielding tensor (CST) of the amide nitrogens in Aib and in conventional amino acids. Here the density functional theory (DFT) based calculations were applied to the known crystal structure of one of peptaibols, Ampullosporin A, in order to explicitly describe the variation of the 15N NMR parameters within its backbone. Based on the DFT computational data it was possible to verify the validity of the assumptions previously made about the differences between Aib and other amino acids in the isotropic part of the CST. Also the trends in the magnitudes and orientations of the anisotropic components of the CST, as revealed by the DFT calculations of the full periodic structure of Ampullosporin A, were thoroughly analyzed, and may be employed in future studies of peptaibols.
Keywords: Peptaibols; peptaiboly; peptidy; antiinfekční látky; Nuclear Magnetic Resonance, Biomolecular; Anti-Infective Agents; nukleární magnetická rezonance biomolekulární; Peptides; Nitrogen Isotopes; izotopy dusíku